Integrated modelling and design for realizing a two-wheeled wheelchair for disabled - Altalmas, Tareq, M.K.; Aula, Abqori; Ahmad, Salmiah; Tokhi, Mohammad Osman; Akmeliawati, Rini (Taylor & Francis, 2016)
Two-wheeled wheelchairs are considered highly nonlinear and complex systems. The systems mimic a double-inverted pendulum scenario and will provide better manoeuvrability in confined spaces and also to reach higher level of height for pick and place tasks. The challenge resides in modelling and control of the two-wheeled wheelchair to perform comparably to a normal four-wheeled wheelchair. Most common modelling techniques have been accomplished by researchers utilizing the basic Newton’s Laws of motion and some have used 3D tools to model the system where the models are much theoretical and quite far from the practical implementation. This paper is aimed at closing the gap between the conventional mathematical modelling approaches where the integrated 3D modelling approach with validation on the actual hardware implementation was conducted. To achieve this, both nonlinear and a linearized model in terms of state space model were obtained from the mathematical model of the system for analysis and, thereafter, a 3D virtual prototype of the wheelchair was developed, simulated and analysed. This have increased the confidence level for the proposed platform and facilitated the actual hardware implementation of the two-wheeled wheelchair. Results show that the prototype developed and tested has successfully worked within the specific requirements established.